2007
DOI: 10.2527/jas.2006-049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water and diet acidification with and without antibiotics on weanling pig growth and microbial shedding1,2

Abstract: Two 5-wk experiments were conducted to determine the effects of water and diet acidification with and without antibiotics on weanling pig growth performance and microbial shedding. In Exp. 1, 204 pigs (19.2 d of age) were used in a 3 x 2 factorial, with 3 dietary treatments fed with or without water acidification (2.58 mL/L of a propionic acid blend; KEM SAN, Kemin Americas, Des Moines, IA). Dietary treatments were: 1) control, 2) control + 55 ppm of carbadox (CB), and 3) dietary acid [DA; control + 0.4% organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 17 publications
3
55
1
2
Order By: Relevance
“…The addition of organic acids to pig diets has been examined for decades, clearly demonstrating to improve growth performance and apparent total tract digestibility (Suryanarayana et al, 2012). Walsh et al (2007) demonstrated that addition of 0.4% organic acid blend (fumaric, lactic, propionic, citric, and benzoic acids) to the diets of nursery pigs resulted in better growth rate, feed intake, and feed efficiency compared with the control diet. In the present study, there was no significant difference in the pre-and post-farrowing body weight and weaning body weight of sows.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of organic acids to pig diets has been examined for decades, clearly demonstrating to improve growth performance and apparent total tract digestibility (Suryanarayana et al, 2012). Walsh et al (2007) demonstrated that addition of 0.4% organic acid blend (fumaric, lactic, propionic, citric, and benzoic acids) to the diets of nursery pigs resulted in better growth rate, feed intake, and feed efficiency compared with the control diet. In the present study, there was no significant difference in the pre-and post-farrowing body weight and weaning body weight of sows.…”
Section: Discussionmentioning
confidence: 99%
“…Os dados do presente experimento estão de acordo com alguns trabalhos, em que a adição de extratos vegetais (Gardiner et al, 2008;Manzanilla et al, 2006) ou ácidos orgânicos (Biagi et al, 2006;Manzanilla et al, 2006;Omogbenigun et al, 2003;Silva, 2002;Walsh et al, 2007aWalsh et al, , 2007b qualquer efeito no pH do conteúdo do trato digestório ou das fezes dos animais. Por outro lado, alguns autores encontraram reduções no pH do conteúdo estomacal (Bolduan et al, 1988a(Bolduan et al, , 1988bRadcliffe et al, 1998;Risley et al, 1992;Tomlinson e Lawrence, 1981), do ceco (Braz, 2007) e do cólon (Manzanilla et al, 2004;Namkung et al, 2004) de animais que receberam ácidos orgânicos em suas dietas.…”
Section: Tabela III Médias De Peso Vivo Inicial (P1) Peso Vivo Aos unclassified
“…As an organic acid, benzoic acid (BA) had strongest antimicrobial effect which may be of interest to reduce diarrhoea incidence of piglets after weaning (Knarreborg et al 2002;Walsh et al 2007). Previous studies have confirmed that inclusion of 0.5-1.0% BA could improve growth performance (Kluge et al 2006;Torrallardona et al 2007) and protein digestibility (Guggenbuhl et al 2007) in weanling pigs.…”
Section: Introductionmentioning
confidence: 99%